Perú y España, política exterior peruana 1968-1975 - Puertas Porras, Elizabeth (2007)
In the XX century the foreign policy of Peru was characterized for its Panamericanism conservative for which reason in the context of Cold War Peru held a close relationship with U.S.A. The foreign policy of Peru was favorable to conservative and authoritarian government of Franco in Spain (1936-1975). The government of Velasco (1968-1975) changed the traditional foreign policy and developed an autonomous foreign policy to USA which did not affect its relationship with Spain but increased it and thus Peru and Spain signed several agreements of technical and cultural cooperation.